Transformer Oil Temperature Detection Utilising a Thermal Resistor Sensor - Muhamad Fauzi, Abdul Azim; Ngajikin , Nor Hafizah; Yaacob, Maslina; Ali, Siti Hajar Aminah (Evolution in Electrical and Electronic Engineering, 2023)
This project aims to design and develop a thermal resistor-based transformer oil temperature detection system with high accuracy. The power transformer is a crucial component in the electrical power system, and monitoring its health is essential for maintaining an uninterrupted supply of electricity. The oil-immersed type of transformer uses mineral oil as a cooling medium to prevent failure due to high temperatures. Temperature detection is necessary to ensure that the transformer operates within safe temperature limits, per industry standards and regulations. This project proposes the use of a thermal resistor-based sensor known as the DS18B20 for temperature detection in transformer oil. Testing of the developed sensor has been carried out using a mineral-based transformer oil with a refractive index value of 1.4732, 1.4782, and 1.4786 which has been heated using the hot plate. The temperature sensor output voltage was recorded and analysed for a temperature range of 30℃ to 80℃. The sensitivity of the sensor in measuring transformer oil temperature is 0.0209mV/℃ for both refractive index values of 1.4732 and 1.4782. For the transformer oil with a refractive index value of 1.4786, the sensitivity of the sensor is 0.0210mV/℃. The sensor system tested on all the oil samples exhibited a high linearity performance of 0.99 with 99.1% accuracy. The sensor compatibility for each sample achieves a promising value in its sensitivity, linearity and accuracy performances.